Pengembangan Bahan Ajar Digital Berbantuan Aplikasi Animaker Pada PAUD Di Kabupaten Pandeglang - Munawar, Badri; Hasyim, Ade Farid; Ma’arif, Minhatul (Jurnal Golden Age, 2020)
This study aims to see the increase in the use of digital teaching materials assisted by Animaker applications for PAUD teachers in Pandeglang Regency. The use of animation in learning process is to enrich the creativity of teachers in the technological era. The problem that occurs in the education process in PAUD is the lack of access to operate digital-based teaching materials, even though facilities are available such as laptops or projectors. The learning process carried out in early childhood education seems boring. For this reason, learning using animated videos is expected to easily enrich teaching materials for teachers. Researchers used the ADDIE model (Analysis, Design, Develop, Implementation, and Evaluation). The research subjects were 30 PAUD teachers in Pandeglang Regency. The results of the research conducted at the evaluation stage showed as much as 85.2% which can be categorized as very high. Digital teaching materials use the help of an effective Animaker application for PAUD teachers.